How speaking correction techniques affect the learning process of intermediate and advances english students in the Foreign Languages Department of the University of El Salvador - Alfaro Meléndez, Rosa del Carmen (Universidad de El Salvador, 2007)
The English language as a lingua franca is a necessary tool nowadays in any field; but to learn English is not as simple as it seems to be. Since it is learned by a process in which English comes into contact with the learners’ mother tongue, it causes a confusion which provokes mistakes in a learner’s use of English. Mistakes are products of the learner’s effort to produce language despite prior knowledge (Simon Mumford and Steve Darn 2005). These mistakes can be at the level of listening, speaking and writing. Julian Edge (1989) suggests that mistakes can be divided into three categories: slips (mistakes which students can correct themselves once the mistakes have been pointed out to them), errors (mistakes which they can not correct themselves and which therefore need explanation), and attempts (that is when a student tries to say something but s/he does not know yet the correct way of saying it). Besides the mistakes aforementioned, teachers must know the importance of correction. If students are not corrected during their learning process they can fossilize and drag those mistakes to Intermediate and Advanced English levels. Mistake correction plays a useful role in order to avoid incorrectness or fossilization in their target language acquisition experience. Another trouble that students face in their learning process is interlanguage, which according to Corder (1978) and Selinker (1974), characterize it as something that is similar to what is spoken by other language learners, but different from target language norms. In Selinker’s view, interlanguage is an intermediate system located on a continuum stretching from the mother tongue to the target language.